Pure sociology and social geometry as an example of formal sociological theory - Škorić Marko; Kišjuhas Aleksej (Sociološki Pregled, 2012)
This paper analyzes pure sociology and social geometry of Donald Black as an example of formal sociological theory. Starting with the importance of formal and analytical theory in sociology, we present the bold theoretical strategy and/or the paradigm of the sociology of behavior of social life. The examples of pure sociology and social geometry concerning law, violence and homosexuality are presented as well. A review and critique of pure sociology as a scientific formal theory is offered in the end.